Improved short‐term variability in the thermosphere‐ionosphere‐mesosphere‐electrodynamics general circulation model. Issue 8 (6th August 2014) - Häusler, K.; Hagan, M. E.; Baumgaertner, A. J. G.; Maute, A.; Lu, G.; Doornbos, E.; Bruinsma, S.; Forbes, J. M.; Gasperini, F.
Abstract We report on a new source of tidal variability in the National Center for Atmospheric Research thermosphere‐ionosphere‐mesosphere‐electrodynamics general circulation model (TIME‐GCM). Lower boundary forcing of the TIME‐GCM for a simulation of November–December 2009 based on 3‐hourly Modern‐Era Retrospective Analysis for Research and Application (MERRA) reanalysis data includes day‐to‐day variations in both diurnal and semidiurnal tides of tropospheric origin. Comparison with TIME‐GCM results from a heretofore standard simulation that includes climatological tropospheric tides from the global‐scale wave model reveal evidence of the impacts of MERRA forcing throughout the model domain, including measurable tidal variability in the TIME‐GCM upper thermosphere. Additional comparisons with measurements made by the Gravity field and steady‐state Ocean Circulation Explorer satellite show improved TIME‐GCM capability to capture day‐to‐day variations in thermospheric density for the November–December 2009 period with the new MERRA lower boundary forcing.